The effects of dual-strain probiotics on the weight gain in premature neonates of Kabul City: A randomized clinical trial - Mansoor Aslamzai; Mohammad Farouq Hamidi; Atiqullah Halimi (Elsevier, 2023)
Background: Prematurity is prevalent worldwide and accounts for the leading cause of neonatal death. Preterm neonates face numerous challenges, including slow weight gain, prolonged hospital stays, and high mortality. Dual-strain probiotics containing Bifidobacterium bifidum and Clostridium butyricum can manage such complications of prematurity. Therefore, the present study was conducted to evaluate the effectiveness of dual-strain probiotics consisting of Bifidobacterium bifidum and Clostridium butyricum on the weight gain of preterm neonates in Kabul City. Methods: This randomized clinical trial was conducted at the Neonatal Units of Malalai Maternity and Maiwand Teaching Hospitals in Kabul City. Finally, 84 preterm neonates were assessed for the effects of dual-strain probiotics. The clinical parameters were daily weight gain and the risks of feeding intolerance and neonatal mortality. Statistical analysis was performed by SPSS 26. Results: Forty-two premature neonates in the probiotics group and another forty-two preterm babies in the control group were investigated. In the probiotic group, 250 mg or 25 × 108 CFU of dual-strain probiotics dissolved in 1-3 ml milk were given twice daily for three weeks. At the time of intervention, the preterm neonates in the probiotics versus control group had a mean age of (7 ± 3.3 vs 6.8 ± 3.3 days; P = 0.69), weight of (1497.5 ± 272 vs 1483.3 ± 271 g; P = 0.8) and gestational age of (33.6 ± 2 vs 33 ± 2.4 weeks; p = 0.31). Gender distribution in the probiotics group was (boys 54.8%, girls 45.2%) and in the control group it was (boys 50%, girl 50%). The premature newborns in the probiotics versus control group had a higher mean daily weight gain (15.5 ± 9.4 vs 10 ± 7.9 g; P = 0.001), lower mean age to reach full enteral feeds (8.74 ± 3.08 vs 10.81 ± 3.43 days, P = 0.005) and lower mean hospital stays (10.02 ± 4.68 vs 12.81 ± 4.86 days, P = 0.009) . The risk ratios of feeding intolerance and mortality during the hospital stays were (RR=0.59, P = 0.71) and (RR=0.67, P = 0.5) in probiotics and non-probiotics groups respectively. Conclusion: Dual-strain probiotics consisting of Bifidobacterium bifidum and Clostridium butyricum significantly improved the daily weight gain, and decreased the time to full enteral feeding and admission days for premature neonates.